Women land rights and food security status of farming households in Oyo State, Nigeria (2020)
The dominance of men in decision-making processes and leadership positions within the communities has made land allocation, land use, and control skewed in favour of men. This study examined the effects of women’s land rights on households’ food security status using a sample of 300 representative farmers. Descriptive statistics, household food expenditure, logistic regression, and ordered logit models were the analytical tools used. Results revealed that about 35% of the rural women farmers had land use rights while the remaining 65% had land ownership rights. Women with ownership rights were more food secure, with the majority of the women having residual rights, while only a few had sell rights. Secure women land rights are germane to achieving and sustaining household and national food security. Strategies and instruments for protecting women rights should be developed and implemented, while efforts geared towards designing strategies, assessing multiple dimensions of women empowerment for improved food security status, and welfare of the households should be intensified.